The Sikh world - Singh, Daljit; Smith, Angela (Hodder Wayland London, 2001)
Tracing the history of the Sikh, this book goes on to uncover what it means to be a practising Sikh in the modern world. It describes the gurdwara, the Sikh holy book, the ceremonies and festivals, and rites of passage